Estimation and Inference by Stochastic Optimization: Three Examples. - FORNERON, JEAN-JACQUES; NG, SERENA (AEA Papers & Proceedings, 2021)
The article discusses about Stochastic Optimization. Topics of discussion includes Bootstrap inference approximates the asymptotic distribution but requires repeated optimization. Newton-Raphson algorithm provides consistent estimates and valid standard errors in optimizer. A resampling-based indirect inference estimator produces standard errors but is efficient by classical optimization.